(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article emphasizes the importance of the cooperation of speech therapists, teachers, psychologists and parents in increasing the effectiveness of correctional work. The results of the study are of great practical importance in improving the process of working with children with speech disorders, supporting their speech and communicative development.